Respostas
respondido por:
1
Razão da PA ( r )
an = ak + ( n - k ).r
3 = 25 + ( 4 - 15 ) . r
3 = 25 - 11.r
3 - 25 = -11. r
-22 / -11 = r
r = 2
====
an = a1 + ( n - 1 ) . r
3 = a1 + ( 4 - 1 ) . 2
3 = a1 + 3 . 2
3 = a1 + 6
3 - 6 = a1
a1 = -3
an = ak + ( n - k ).r
3 = 25 + ( 4 - 15 ) . r
3 = 25 - 11.r
3 - 25 = -11. r
-22 / -11 = r
r = 2
====
an = a1 + ( n - 1 ) . r
3 = a1 + ( 4 - 1 ) . 2
3 = a1 + 3 . 2
3 = a1 + 6
3 - 6 = a1
a1 = -3
ananknolfc:
Obrigado !
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás